Program Interaktif Bisnis Sebagai Strategi Motivasi Kewirausahaan di Masa Pandemi Covid 19 - Barotun Mabaroh; Nunuk Indarti; Dies Nurhayati; Ana Ahsana El Sulukiyyah; Diah Anita Pusparini (PT FORMOSA CENDEKIA GLOBAL, 2022)
The Covid 19 pandemic has significant impacts on all circles of society, especially small business owners (IKM). Responding to this condition, the team collaborating with Business Development Center (P2B) of PGRI Wiranegara University organized Interactive Business Program through Google Meeting. This program was open for IKM owners, students, and the public. This Interactive Business Program was carried out in January and February 2021. This program aimed at sharing experiences on how to maintain a business and or start a new business during the pandemic. The team initiated the topics on Business and the Action Plan, and Developing Village-Owned Enterprises and Modernization of Retail Businesses. This program resulted in the participants’ development on enterpreunerial skills and motivation to operate the business.